2012
DOI: 10.1093/heapro/das025
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness and mediators of a need-supportive physical activity coaching among Flemish sedentary employees

Abstract: This study examined the long-term and mediation effects of a need-supportive coaching programme on physical activity. Sedentary employees (n = 92) of the university of Leuven received 4 months of physical activity coaching, based on the self-determination theory, by coaches with a bachelor's degree in kinesiology who are specializing in health-related physical activity (n = 30). The programme consisted of a limited number of individual contact moments (i.e. an intake session, three follow-up contacts and an ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…In this respect, our intervention resulted in significant improvement in identified regulation for PA (i.e., valuing the benefits of PA), which is consistent with previous studies that targeted HIV uninfected participants (Silva et al, 2011; Silva et al, 2010; Van Hoecke et al, 2013). There was not a statistically significant improvement in intrinsic regulation for PA (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…In this respect, our intervention resulted in significant improvement in identified regulation for PA (i.e., valuing the benefits of PA), which is consistent with previous studies that targeted HIV uninfected participants (Silva et al, 2011; Silva et al, 2010; Van Hoecke et al, 2013). There was not a statistically significant improvement in intrinsic regulation for PA (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…Implementing intentions based on these questions has been shown to be effective in previous studies [27, 38]. …”
Section: Methodsmentioning
confidence: 99%
“…In a randomized controlled trial among insufficiently active university employees, Van Hoecke et al found significant positive long-term effects of a 4-month need-supportive PA coaching intervention on moderate, vigorous and total PA [27]. The present study elaborates on that intervention by implementing additional self-monitoring tools including pedometers and PA diaries.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Over the recent past years, quite a few counselling PA interventions that combine the theoretical framework of SDT with the practical strategies from MI have been developed and evaluated in randomized controlled trials (Duda et al, 2014;Fortier, Duda, Guerin, & Teixeira, 2012;Fortier et al, 2007Fortier et al, , 2011Jolly et al, 2009;Silva et al, 2011Silva et al, , 2008Van Hoecke, Delecluse, Bogaerts, & Boen, 2014;Van Hoecke et al, 2013). In general these studies show that SDT/MI-based PA interventions can be effective in increasing PA.…”
Section: Self-determination Theory and Motivational Interviewingmentioning
confidence: 99%